REKONSILIASI RENCANA SEQUENCE PENAMBANGAN DENGAN REALISASI DI PIT X PADA BULAN MEI 2021 DI PT. BUKIT ASAM,TBK. TANJUNG ENIM, SUMATERA SELATAN - Didan Ramaddandy; Rizto Salia Zakri (Departemen Teknik Pertambangan FT UNP, 2021)
During mining sequences at Pit X, PT. Bukit Asam,Tbk incompatibilities over-stripping, overcut, and undercut frequently happen as a result of the reconciliation between mine plan design with realization in the field. These incompatibilities can be happened repeatedly every month due to undercut material, proven by the reconciliation data on March and April 2021. So there needs a reconciliation on May 2021 to figure out incompatibility between mine plan design with the realization, obtain the causing factors and solutions to minimize incompatibilities occurred. The analysis to find out the incompatibilities on May 2021 was carried out by overlay the mine progress map with mineplan design, creating cross-sections, calculating the volume from the latest mining activity of the month, analyzing causing factors with the actual data to obtain the solutions of the problems. Analysis results proved that on May 2021 over-stripping, overcut, and undercut incompatibility sequentially occurred for overburden of 226.950,79 BCM, 147.927,12 BCM, and 491.891,14 BCM, while for coal it is 59.249,65 Tons, 77.733,18 Tons, and 134.776,15 Tons. From the analysis, the causes of the incompatibilities are the number and placement of fleets that don’t base on the plan, low productivity of digging and loading equipment, incompatibility of mechanical equipment used, and supervision factors. Those incompatibilities affect the increase of the stripping ratio for the next month’s plan. Several actions can be done such as replacing digging and loading equipment on both fleets with higher specifications, adding mining boundaries, and improving supervisions in the field to minimize the incompatibilities.